Effects of mouse predation on burrowing petrel chicks at Gough Island. Issue 6 (30th June 2015) - Dilley, Ben J.; Davies, Delia; Bond, Alexander L.; Ryan, Peter G.
Abstract: Since 2004 there has been mounting evidence of the severe impact of introduced house mice ( Mus musculus L.) killing chicks of burrow-nesting petrels at Gough Island. We monitored seven species of burrow-nesting petrels in 2014 using a combination of infra-red video cameras augmented by burrowscope nest inspections. All seven camera-monitored Atlantic petrel ( Pterodroma incerta Schlegel) chicks were killed by mice within hours of hatching (average 7.2±4.0 hours) with an 87% chick failure rate ( n =83 hatchlings). Several grey petrel ( Procellaria cinerea Gmelin) chicks were found with mouse wounds and 60% of chicks failed ( n =35 hatchlings). Video surveillance revealed one (of seven nests filmed) fatal attack on a great shearwater ( Puffinus gravis O'Reilly) chick and two (of nine) on soft-plumaged petrel ( Pterodroma mollis Gould) chicks. Mice killed the chicks of the recently discovered summer-breeding MacGillivray's prion ( Pachyptila macgillivrayi Mathews), with a chick mortality rate of 82% in 2013/14 and 100% in 2014/15. The closely-related broad-billed prion ( P. vittata Forster) breeds in late winter and also had a chick mortality rate of 100% in 2014. The results provide further evidence of the dire situation for seabirds nesting on Gough Island and the urgent need for mouse eradication.